Mixed methods study exploring parent engagement in child health research in British Columbia. Issue 5 (1st June 2019) - Smith, Jennifer; Pike, Ian; Brussoni, Mariana; Tucker, Lori; Mâsse, Louise; Mah, Janet W T; Boudreau, Ainsley; Mount, Dawn; Bonaguro, Russell; Glegg, Stephanie; Amed, S
Abstract : Objectives: The objective of this study was to explore parent perspectives of and interest in an interactive knowledge translation platform called Child-Sized KT that proposes to catalyse the collaboration of patients, families, practitioners and researchers in patient-oriented research at British Columbia Children's Hospital (BCCH). Methods: An explanatory sequential mixed methods design was used over 1 year. Over 500 parents across BC completed an online survey, including a subsample of 102 parents who had accessed care at BCCH within the past 2 years. The survey explored parent perspectives about the value of their engagement at all stages of the research process and their interest in and concerns with using an online platform. Following the online survey, two focus groups were held with parents in the Vancouver area to explore themes emerging from the survey. Results: Parents expressed keen interest in engaging in research at BCCH. Parents perceived benefit from their input at all stages of the research process; however, they were most interested in helping to identify the problem, develop the research question and share the results. Although parents preferred online participation, they had concerns about protecting the privacy of their child's information. Conclusions: Parents see value in their involvement in all stages of child health research at BCCH. Their input suggests that Child-Sized KT, a hypothetical online platform, would facilitate meaningful stakeholder engagement in child health research, but should offer a customised experience and ensure the highest standard of data privacy and protection.